Mechanical property testing and damage assessment of the regenerated rock mass with very weakly bonded cement - Wang, Ping; Jiang, Yongzhi; Ding, Li; Li, Peng; Wu, Huan; Zhou, Ze; Zhou, Jinlian; Zhang, Xiangyang (Frontiers in Built Environment, 2024)
The regenerated rock mass is a bearing structure formed by natural compaction in a hollow area, and the investigation of its optimal consolidation material and consolidation parameters is the key to improving the supporting effect and bearing stability of roadways. The effects of consolidation materials and parameters on the stability of the regenerative rock mass were studied using laboratory tests, numerical simulations, and theoretical analyses. Acoustic emission was used to monitor the variation characteristics of energy and ringing count during the process of rock mass failure, and the bonding interface area of the extremely weak cementation regeneration structure was tested by electron microscope scanning. The results show that there is a quadratic function relationship between the water–cement ratio of different cementing materials and the bond strength of the recycled rock mass; the regenerative rock mass with superfine cement exhibited the highest compressive strength and the largest cumulative energy of acoustic emission. This shows that it has the strongest bearing capacity, the highest elastic performance, the most stable micro-fracture development, and the best cementation effect, followed by ordinary cement, gypsum, and laterite. The scanning test showed that the regenerated structure had more internal pores, a loose structure, and poor cementation. Three-dimensional scanning modeling of four representative broken rock blocks was carried out, and the simulation verified that the regenerated structure had macroscopic “X”-shaped shear failure characteristics. The numerical simulation also verified three forms of rupture in the regenerative structure detected by electron microscopy scanning. Exploring the mechanism of action of the regenerative rock mass in the goaf provides a certain reference value for the stability control of the regenerated rock mass roadway.